Influência do compartilhamento de informações, capital psicológico e engajamento no trabalho na relação entre participação orçamentária e o desempenho gerencial - Machado, Fernanda Souto (2022)
This research evaluates the influence of information sharing, psychological capital and work engagement on the relationship between budgetary participation and managerial performance of controllers of industrial companies operating in Brazil. The research is classified as descriptive, with a quantitative approach, carried out through a survey, with the application of a questionnaire through the LinkedIn® business network. The individuals participating in the study play the role of controller, controllership manager or controllership coordinator. The sample consisted of 261 managers with budgetary responsibility who perform this function. The theoretical relationships investigated in this research were tested using the structural equation modeling technique. The results found showed a direct and positive influence of budgetary participation on information sharing and engagement at work, but not significant on psychological capital and managerial performance, which suggests that the effects of budget participation on performance may not occur directly, but from other intervening variables and their joint interactions. Information sharing proved to be able to directly and positively influence psychological capital and managerial performance, but it does not have a direct and significant influence on work engagement. It was also observed that the positive psychological capabilities that make up the psychological capital of controllers directly and positively influence managerial performance and engagement at work, which in turn also has a positive influence on managerial performance. The interactions between information sharing, psychological capital and work engagement positively reflect the effects of budgetary participation on managerial performance, suggesting under which conditions budgetary participation will exert a positive influence on managerial performance. The research results converge with what is advocated in the Social Cognitive Theory, indicating that human behavior and action in the budgetary context are influenced by an interaction between different factors (cognitive and personal, behavioral and environmental). It is concluded that a participatory budgeting configuration involves managers in the preparation of the budget, stimulating the sharing of information and organizational communication. This communication enhances the controllers' positive psychological capabilities of self-efficacy, hope, optimism and resilience, which is why their engagement at work is enhanced, resulting in better managerial performance. This evidence also reveals that budgetary participation alone may not be enough to ensure better managerial performance. These findings contribute to a more appropriate choice of budget management practices that influence the cognition, behavior and performance of managers at work, as well as contributing to controllers in the knowledge of constraints of their managerial performance in the budgetary context.